(untitled) (Research, Society and Development, 2022)
Develop a mobile application for cell phones, to facilitate the prescription of preparations for imaging exams by nurses and the orientation of these preparations to users who access the Division of Diagnostic Imaging (DDI) of the Ophir Loyola Hospital. Study applied in the modality of technological, descriptive production, with a qualitative approach, using the Contextualized Instructional Design (DIC) model for the development of an application. The DIC is adopted to describe a constructive proposal in the intentional action of planning, contextualizing the contents and tools available by Information and Communication Technologies (ICT’s). In view of the responses received, it was possible to verify that the mobile application should be based on objectivity and ease of navigation, as well as clear information and language accessible to all audiences. AMEI/HOL presents a clear and objective navigation area for easy access. In this way, there was the construction of the mobile application based on the reality experienced by the health institution, updating an obsolete protocol and on the main doubts of the target audiences regarding the theme, as a way of achieving maximum public satisfaction and also the objectives of the study here proposed.